2022
DOI: 10.1097/mrr.0000000000000534
|View full text |Cite
|
Sign up to set email alerts
|

Does kinesiophobia obstacle to physical activity and quality of life in asthmatic patients?

Abstract: Kinesiophobia has been studied in musculoskeletal and neurological diseases. The aim of this descriptive study was to assess the level of kinesiophobia in stable asthmatic patients, and to determine whether it is an obstacle to physical activity and quality of life. A total of 62 asthmatic patients and 50 healthy control subjects were assessed using the tampa kinesiophobia scale (TSK) for kinesiophobia, International Physical Activity Questionnaire-Short Form (IPAQ-SF) for physical activity levels, and Asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…In 54 of the 74 studies, kinesiophobia was assessed using the 17-item TSK (TSK-17; n = 38) 29,62,64,65,68,72,73,77,84,85,90,91,111114,117120,122125,130,133135,138144,146,148,150 shorter versions of the TSK [(TSK-11 152 ; n = 10) 63,81,88,116,121,122,128,131,136,151 , (TSK-14; n = 1) 74 , (TSK-13 153 ; n = 2) 115,137 , (TSK-7; n = 1) 145 ], or its adaptation for patients with coronary artery disease (TSK-Heart 154 ; n = 2) 86,87 . The TSK is a questionnaire that assesses the belief that movements can lead to (re)injury, pain, or aggravation of an underlying and serious medical condition 28 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 54 of the 74 studies, kinesiophobia was assessed using the 17-item TSK (TSK-17; n = 38) 29,62,64,65,68,72,73,77,84,85,90,91,111114,117120,122125,130,133135,138144,146,148,150 shorter versions of the TSK [(TSK-11 152 ; n = 10) 63,81,88,116,121,122,128,131,136,151 , (TSK-14; n = 1) 74 , (TSK-13 153 ; n = 2) 115,137 , (TSK-7; n = 1) 145 ], or its adaptation for patients with coronary artery disease (TSK-Heart 154 ; n = 2) 86,87 . The TSK is a questionnaire that assesses the belief that movements can lead to (re)injury, pain, or aggravation of an underlying and serious medical condition 28 .…”
Section: Resultsmentioning
confidence: 99%
“…All studies provided the accelerometer or pedometer on the day kinesiophobia was assessed (n = 18) 63,65,66,75,78,88,89,111,113,120,122,126,132,137,143,148,150 . The remaining studies did not specify whether kinesiophobia was measured the day the device was provide or the last day of physical activity assessment (n = 7) 74,118,124,128,144,146,151 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24,46,49,50] However, with the development of medicine, the study of kinesiophobia had long been associated with a variety of different types of pain-related diagnoses. [8–12] We believe that special measurement tools for kinesiophobia for special diagnoses can be one of the directions of future research.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Review of the literature revealed that in addition to patients with chronic back pain, who commonly experience kinesiophobia, other diseases accompanied by pain, such as Parkinson disease, fatigue, heart disease, temporomandibular joint disease, scoliosis, and even asthma and stroke may also lead to kinesiophobia. [8][9][10][11][12] Due to the diversity and complexity of the risk factors and neurophysiological mechanisms of kinesiophobia, [13,14] which have a profound impact on the physical and mental health and quality of life of patients, [5,8] in-depth understanding and analysis of kinesiophobia remains a top priority in future work to develop more targeted and effective screening, prevention and treatment strategies. Ultimately, the health outcomes and quality of life of kinesiophobia patients may be improved, and the burden on family and society may be reduced.…”
Section: Introductionmentioning
confidence: 99%